2006 IEEE MTT-S International Microwave Symposium Digest 2006
DOI: 10.1109/mwsym.2006.249894
|View full text |Cite
|
Sign up to set email alerts
|

An LTCC-based Wireless Transceiver with Integrated Optical Interface

Abstract: This paper describes the realization of an LTCC based optical wireless-transceiver using radio-over-fiber (RoF) techniques. For the first time, single mode optical fibers are employed, making this device particularly attractive for indoor and outdoor distributed antenna systems. The operating frequencies are in the 5-6 GHz band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…LTCC-based optical transceivers using single mode fibers have already been investigated [1], [2] and it was shown that they can be used for long distance links in RoF networks.…”
Section: Introductionmentioning
confidence: 99%
“…LTCC-based optical transceivers using single mode fibers have already been investigated [1], [2] and it was shown that they can be used for long distance links in RoF networks.…”
Section: Introductionmentioning
confidence: 99%
“…The development of compact modules that intimately combine the antenna and transceiver electronics is receiving increasing interest, although the LTCC receiver presented in [4] does not contain the antenna. Advances in circuit miniaturization and packaging technology have made the goals of Manuscript smaller size and lighter weight attainable for a general packet radio service (GPRS) mobile application [5].…”
Section: Introductionmentioning
confidence: 99%